Linking Internal Capabilities and External Conditions: A Systematic Review of SME Financial Performance in Indonesia - Ghiyats Furqan Dewantara; Saras Shinta Qurrota'Aini; Khalilul Rahman; Fandi Galang Wicaksana (Jurnal Manajemen Sains dan Organisasi, 2026)
Objective – This study aims to examine the factors influencing the financial performance of small and medium enterprises (SMEs) in Indonesia. It focuses on identifying key internal and external factors and analyzing their interaction through mediating and moderating mechanisms. Design/Methodology/Approach – This study uses a systematic literature review (SLR) with the PRISMA framework. Articles were sourced from the Scopus database using predefined criteria. Through identification, screening, eligibility, and inclusion stages, 17 relevant studies were selected. Findings – The findings show that SME financial performance is influenced by both internal and external factors. Internal factors, such as financial literacy and intellectual capital, are often latent and do not directly affect performance. External factors, including market conditions and access to funding, help translate these internal capacities into measurable outcomes. Conclusion and Implications – The study concludes that financial performance depends on the interaction between internal capabilities and external conditions. SMEs need to align both to improve performance. Future research should develop more integrated models to capture these relationships.